Reaching High Altitudes on Mars with an Inflatable Hypersonic Drag Balloon (Ballute) - Griebel, Hannes; SpringerLink (Online service) (Wiesbaden : Vieweg+Teubner, 2010)
The concept of probing the atmosphere of planet Mars by means of a hypersonic drag balloon, a device known as a (3z(Bballute(3y(B, is a novel approach to planetary science. In this concept, the probe deploys an inflatable drag body out in space and may then enter the atmosphere either once or several times until it slowly descends towards the ground, taking continuous atmospheric and other readings across a large altitude and ground range. Hannes Griebel discusses the theory behind such a mission along with experience gained during its practical implementation, such as mission design, manufacturing, packing and deployment techniques as well as ground and flight tests. The author also studies other ballute applications, specifically emergency low Earth orbit recovery and delivering payloads to high altitude landing sites on Mars.s
Related Technologies and State of the Art -- Basic Considerations on Probes with Low Ballistic Coefficients -- Ballute Spacecraft Configuration options -- Flight Dynamics Analysis -- Material Analysis -- Ballute -- Transportation and Deployment System -- Inflation Control and Gas Storage System (IGSS) -- Mission and Spacecraft Design for Ballute Applications -- Conclusion and Outlook.
Keywords: Physics; Physics; Physics, general